A comparative study of irradiation response in amorphous TaTiWVCr refractory high entropy alloy with the counterpart of tungsten films. (May 2023) - Pu, Guo; Sun, Sen; Wang, Sishu; Gan, Lin; Chen, Sheng; Ye, Zongbiao; Huang, Zhangyi; Zheng, Jiaochun; Wang, Zhijun; Yang, Chi; Lin, Liwei; Liu, Bo; et al.
Abstract: In this work, tungsten-containing TaTiWVCr refractory high entropy alloy (RHEA) and tungsten (W) films with amorphous structures were irradiated by a 60 keV helium (He) ion beam platform, the fluences were ranging from 1 × 10 16 cm −2 to 2 × 10 17 cm −2 . Results showed that the crystallization phenomenon in RHEA initially happened at fluence of 5 × 10 16 cm −2 . Meanwhile, the obvious crystallization in W films was induced at the highest fluence of 2 × 10 17 cm −2 . This indicated that the crystallization and the grain growth in TaTiWVCr RHEA amorphous films were more easily occurred than that of W films when exposed to the same He + environment. The prominent electronic stopping power and He + energy deposition induced electron excitation played vital role in producing inelastic thermal-spikes via electron-phonon coupling, which was contributed to the crystallization kinetic energy and the overall grain growth in irradiated regions. The phase structure of RHEA film kept stable up to the highest fluence of 2 × 10 17 cm −2, even though the alloy elements demonstrated local short-range segregation due to the diffusion-driven crystallization and the formation of highly-pressurized bubbles in the irradiated RHEA. In contrast to the W, smaller-sized bubbles and less dislocations were mainly distributed in the irradiated region of RHEA due to its naturally special high entropy effect and high lattice distortion. Besides, the results of irradiation-induced superficial morphology and volume swelling revealed that the RHEA exhibited more excellent swelling resistance than that of W. This study will potentially provided a useful indicator of RHEA with self-healing stability to resist irradiation and promote the development of state-of-the-art plasma-facing materials for the future nuclear fusion. Graphical abstract: Image 1 Highlights: The crystallization in TaTiWVCr refractory high entropy alloy (RHEA) was more easily than that of W. Smaller-sized He bubbles and the fewer dislocations were revealed in the irradiated region of RHEA than W. The phase structure kept stable in RHEA while the elements demonstrated local short-range segregation. The RHEA exhibited more excellent swelling resistance than the counterpart of W.